Determinación del mercado objetivo y la demanda insatisfecha, cuando no se dispone de estadísticas - Toapanta Ramos, Luis Fernando (2011)
The business plan and / or feasibility study represents the best investment alternative, with a level of return greater than the opportunity cost of capital. When the return of the project is greater than the opportunity cost, means sustaining the flow of benefits of the project, with the determination of unmet demand and an efficient performance of the project, and consequently, determine the unmet demand is a key element to show the feasibility of the project. There is not always available statistics for the market research of new business opportunities, in this sense, we have developed this methodology, based on a case study for the determination of the target market and unmet when there are no statistics.